Lesson 5: First Order Linear Differential Equations: William Mccallum 6 September 2005
Lesson 5: First Order Linear Differential Equations: William Mccallum 6 September 2005
Lesson 5: First Order Linear Differential Equations: William Mccallum 6 September 2005
Equations
William McCallum
6 September 2005
Introduction
Having seen how to visualize and numerically approximate solutions to dif-
ferential equations, we now look at how to find expressions for the solutions.
What is a Linear Equation?
We consider the simplest sort of differential equation—one which is linear in x
and its derivatives. This means that the only terms in the equation involve 1,
x, x0 , . . . multiplied by functions of t.
A first order linear equation has the form
x0 = p(t)x + q(t).
x0 = t2 x + 3
x0 = tx2 + 3
et x − tx0 = t2
t 0
e x − xx = 3
0
x = rx
x0 = rx − h
x
x0 = rx(1 − )
K
The equation is said to be homogeneous if the constant term, q(t), is zero.
The differential equation
x0 = 3x
is homogeneous, whereas
x0 = 3x + sin t
is inhomogeneous.
The Integrating Factor
1
Consider the homogeneous equation
x0 = 0.1x.
How do we prove that the general solution is x = Ce0.1 ? By proving that xe−0.1t
is a constant.
Want to show that if
x0 = 0.1x (1)
then
d
(xe−0.1t ) = 0
dt
So
d
(xe−0.1t ) = x0 e−0.1t + x(−0.1e−0.1t )
dt
= e−0.1t (x0 − 0.1x)
= 0.
By (1), we have
x0 − 0.1x = 0
If we reverse the order of steps in this proof, we get a method of solving that
works for inhomogeneous equations as well. For example,
x0 = 0.1x − 100
0
x − 0.1x = −100
e−0.1t (x0 − 0.1x) = −100e−0.1t
x0 e−0.1t + (−0.1)e−0.1t x = −100e−0.1t
d
(xe−0.1t ) = −100e−0.1t
dt Z
xe−0.1t = (−100e−0.1t ) dt = 1000e−0.1t + C
x = Ce0.1t + 1000
2
We will try integrating factors of the form e−P (t) , where P (t) is some function.
x0 = t2 x
0 2
x −t x = 0
−t3 /3 0 2
e (x − t x) = 0
0 −t3 /3 2 −t3 /3
xe + (−t )e x = 0
d 3
(xe−t /3 ) = 0
dt
3
xe−t /3 = C
3
x = Cet /3
x0 = p(t)x + q(t)
is
e−P (t)
where Z
P (t) = p(t) dt.
• integrate both sides, using the product rule in reverse on the left
• isolate x
3
x0 = rx − h
x0 − rx = −h
e−rt (x0 − rx) = −he−rt
0 −rt
xe + (−r)e x = −he−rt
−rt
d
(xe−rt ) = −he−rt
dt
Z t Z t
d
(xe−rs ) ds = (−he−rs ) ds
0 ds 0
t
h −rs h h
xe−rt − x0 = e = e−rt −
r 0 r r
h −rt h
xe−rt = e + (x0 − )
r r
h rt h
x = (x0 − )e +
r r